2009
DOI: 10.1001/archoto.2009.43
|View full text |Cite
|
Sign up to set email alerts
|

Novel Integrative Methods for Gene Discovery Associated With Head and Neck Squamous Cell Carcinoma Development

Abstract: With the advent of high-throughput techniques to study cancer genetics, novel comparisons of large data sets using integrative methods may elucidate genetic alterations in HNSCC cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
(48 reference statements)
2
9
0
Order By: Relevance
“…Therefore, the role and potential involvement of the DLEC1 gene in HNSCC remains unknown. In the current study, we observed down-regulation in DLEC1 mRNA expression in 63 of the 97 (64.9%) fresh HNSCC tumor tissue samples supporting the report by Smith et al (2009). However, DLEC1 mRNA was increased in 33% of tumor tissue samples compared to normal tissues.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, the role and potential involvement of the DLEC1 gene in HNSCC remains unknown. In the current study, we observed down-regulation in DLEC1 mRNA expression in 63 of the 97 (64.9%) fresh HNSCC tumor tissue samples supporting the report by Smith et al (2009). However, DLEC1 mRNA was increased in 33% of tumor tissue samples compared to normal tissues.…”
Section: Discussionsupporting
confidence: 89%
“…Zhang et al, 2010;Kwong et al, 2006Kwong et al, , 2007Ying et al, 2009;Smith et al, 2009). In 2009, Smith et al (2009) performed an integrative gene discovery approach to identify the consensus cancer coding sequences in deleted and amplified chromosomal regions in HNSCC. The DLEC1 gene has been identified as one of the putative consensus cancer coding sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the DLEC1 methylation status was correlated with survival in Japanese lung cancer patients. DLEC1 is a candidate tumor-suppressor gene found in multiple cancer types (3)(4)(5)7,15,16). DLEC1 suppresses tumor growth or reduces the invasiveness of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Alleic loss of chromosome 3p is one of the most frequent and earliest documented events in lung cancer with a wide range of 3p mutations (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), suggesting the presence of multiple tumor-suppressor genes on 3p (1)(2)(3). the chromosome locus 3p22.3 is a 'hot spot' for chromosomal aberrations and loss of heterozygosity in cancers, including lung cancer (4,5).…”
Section: Introductionmentioning
confidence: 99%